Preoperative evaluation and perioperative management of patients undergoing major vascular surgery. (October 2022) - Lee, Christopher; Columbo, Jesse A; Stone, David H; Creager, Mark A; Henkin, Stanislav
Patients undergoing major vascular surgery have an increased risk of perioperative major adverse cardiovascular events (MACE). Accordingly, in this population, it is of particular importance to appropriately risk stratify patients' risk for these complications and optimize risk factors prior to surgical intervention. Comorbidities that portend a higher risk of perioperative MACE include coronary artery disease, heart failure, left-sided valvular heart disease, and significant arrhythmic burden. In this review, we provide a current approach to risk stratification prior to major vascular surgery and describe the strengths and weaknesses of different cardiac risk indices; discuss the role of noninvasive and invasive cardiac testing; and review perioperative pharmacotherapies.